Developmental States and Sustainability Transitions: Prospects of a Just Transition in South Africa. Issue 5 (19th October 2016) - Swilling, Mark; Musango, Josephine; Wakeford, Jeremy
Abstract: Since the onset of the global economic crisis in 2007/2008 two key trends have made it necessary to reconceptualize the relationship between development and sustainability: the rapid rise of the so-called 'BRICS' and the emergence of the green economy discourse and now since 2015 the adoption of the Sustainable Development Goals. To address this challenge with respect to developing economies in the global South, this paper endeavours to fuse the core conceptual concerns of the developmental state and sustainability transition literatures. It is argued that a just transition would consist of a dual commitment to human well-being (with respect to income, education and health) and sustainability (with respect to decarbonization, resource efficiency and ecosystem restoration). However, to understand these processes we need a better understanding of political dynamics, and for this purpose the notion of a socio-political regime is introduced. A case study of South Africa's dual developmental and environmental trajectories is presented, revealing how different it is to the East Asian experience. Although a just transition in South Africa is currently unlikely, the rapid emergence of the renewable energy niche signals what may be possible if political and environmental shocks are experienced by key actors within the socio-political regime.